Contrasting Resource-Use Strategies Under Tropical Stress: Linking Leaf Functional Traits to Fruit Biomass and Oil Yield in Camellia Oleifera - Wenjun Hong; Jindian Yang; Shufen He; Jiaming Song; Weiyu Chen; Zhitong Mai; Feifei Chen; Ling Lin; Chuanteng Huang (Tropical Plant Biology, 2026)

Supramolecularly cross-linked aramid-PVDF-aramid sandwich electrolytes with continuous Li+ pathways for ultralong cycle life in solid-state lithium metal batteries - Jianhong Xu; Dehua Li; Xiao Yang; Yingyuan Ma; Xinrui Zheng; Panpan Shen; Di Zhang; Weiyu Teng; Yuting Lin; Yi Hu (Chemical Engineering Journal, 2026)

Integrating social media data and machine learning methods for flash flood susceptibility mapping in China - Yaojie Zhuang; Tuoshi Gong; Jian Fang; Dingtao Shen; Weiyu Tang; Sanming Lin; Xinyi Chen; Yihan Zhang (Journal of Hydrology, 2026)

Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract

Real-time satellite monitoring of the 2024–2025 dyke intrusion sequence at Fentale-Dofen volcanoes, Ethiopia - Lin Way; Juliet Biggs; Weiyu Zheng; Milan Lazecky; Edna W. Dualeh; Tim Wright; Raphaël Grandin; Arthur Hauck; Sue Loughlin; Julia Crummy; Elias Lewi (Bulletin of Volcanology, 2025)

Scientific response to the 2024–2025 dyke intrusions in the Fentale-Dofen Region, Ethiopia: geophysical monitoring, surface manifestations, and hazard mapping - Elias Lewi; Juliet Biggs; Atalay Ayele; Tim Wright; Carolina Pagli; Derek Keir; Yechale Ali; Genet Assefa; Hua Wang; Alessandro La Rosa; Lin Way; Filagot Mengistu; et al. (Bulletin of Volcanology, 2025)
In continental rifts, tectonic deformation, magmatic processes, and earthquakes interact dynamically reflecting the crust’s complex response to extensional stress and evolving subsurface and surface conditions. Recent seismotectonic activity in the Fentale-Dofen region of the Main Ethiopian Rift was driven by the intrusion of several dykes reaching up to ~ 50 km in length observed using satellite radar interferometry. Over 300 earthquakes with magnitude 4 or greater were reported by international seismic networks and the GNSS site at Addis Ababa moved ~ 20 mm to the west. These and other observations on the ground were used to create a highly simplified hazard map and 75,000 people were evacuated. Although no magmatic eruption occurred, the earthquakes triggered landslides and caused infrastructure damage, especially to buildings and roads. Here we provide a preliminary analysis of the patterns of earthquakes, ground deformation, and surface manifestations from 2024 to 2025, with a focus on the underlying mechanisms contributing to seismic sequences in the area and key unresolved scientific questions. We discuss how scientific evidence was used to inform decision-makers and examine the short- and long-term implications for critical infrastructure and nearby communities. Finally, we emphasize the importance of real-time monitoring, proactive risk management, and the need for continuous observation and improved early warning systems to reduce future seismic and volcanic risks.

Variations in optimal seismic intensity measures for shallowly buried bias loess tunnels - Weiyu Sun; Juncen Lin; Bo Wang; Songhong Yan (Journal of Mountain Science, 2025)

Exploring the Impact of Agro-Ecological Efficiency on Poverty Reduction: A Case Study from China - Qing Guo; Weiyu Lin (Environmental Modeling & Assessment, 2025)

Function-Genes and Disease-Genes Prediction Based on Network Embedding and One-Class Classification - Weiyu Shi; Yan Zhang; Yeqing Sun; Zhengkui Lin (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Physiology, microcystin production, and transcriptomic responses of Microcystis aeruginosa exposed to calcium and magnesium - Li Yin; Lin Xu; Kaipian Shi; Weiyu Chen; Yong Zhang; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Science of The Total Environment, 2024)

Novel Selective Quantification of Zinpentraxin Alfa Biotherapeutic in the Presence of Endogenous Isomer in Plasma Samples of Idiopathic Pulmonary Fibrosis Patients Using Immunoaffinity LC–MS - Maoyin Li; Audrey Arjomandi; Xiaowei Sun; Erhu Lu; Tulika Tyagi; WeiYu Lin; Saloumeh K. Fischer; Surinder Kaur; Keyang Xu (The AAPS Journal, 2023)
Idiopathic pulmonary fibrosis (IPF) is a progressive fatal interstitial lung disease that affects three million patients worldwide and currently without an effective cure. Zinpentraxin alfa, a recombinant human pentraxin-2 (rhPTX-2) protein, has been evaluated as a potential drug candidate for the treatment of IPF. Clinical pharmacokinetic analysis of zinpentraxin alfa has been challenging historically due to interference from serum amyloid P component (SAP), an endogenous human pentraxin-2 protein. These molecules share an identical primary amino acid sequence and glycan composition; however, zinpentraxin alfa possesses α2,3-linked terminal sialic acid residues while SAP is an α2,6-linked isomer. By taking advantage of this only structural difference, we developed a novel assay strategy where α2,3-sialidase was used to selectively hydrolyze α2,3-linked sialic acid residues, resulting in desialylated zinpentraxin alfa versus unchanged sialylated SAP, following an immunoaffinity capture step. Subsequent tryptic digestion produced a unique surrogate asialo-glycopeptide from zinpentraxin alfa and allowed specific quantification of the biotherapeutic in human plasma. In addition, a common peptide shared by both molecules was selected as a surrogate to determine total hPTX-2 concentrations, i.e., sum of zinpentraxin alfa and SAP. The quantification methods for both zinpentraxin alfa and total hPTX-2 were validated and used in pharmacokinetic assessment in IPF patients. The preliminary results suggest that endogenous SAP levels remained largely constant in IPF patients throughout the treatment with zinpentraxin alfa. Our novel approach provides a general bioanalytical strategy to selectively quantify α2,3-sialylated glycoproteins in the presence of their corresponding α2,6-linked isomers. Graphical Abstract

The Development and Characterization of a Highly Sensitive Mature TGFβ3 Assay to Evaluate Anti-TGFβ3 Target Engagement - A. Francesca Setiadi; Gizette Sperinde; Melissa Cheu; Wei-Ching Liang; WeiYu Lin; Connie Mahood; Saloumeh K. Fischer (The AAPS Journal, 2023)

A Combined Remediation Strategy of Arsenic and Cadmium in the Paddy Soil of Polymetallic Mining Areas - Longyong Lin; Runliang Zhu; Zhaohui Li; Cunliang Han; Weiyu Li; Yirong Deng (Bulletin of Environmental Contamination and Toxicology, 2021)

Coal pillar size design and surrounding rock control techniques in deep longwall entry - Renshu Yang; Ye Zhu; Yongliang Li; Weiyu Li; Hai Lin (Arabian Journal of Geosciences, 2020)

Discovery of a virus of the species Enterovirus F in goats - Xiaoran Chang; Qian Lin; Junying Hu; Xu Wang; Xin Li; Menglu Cai; Weiyu Wang; Zecai Zhang; Xinping Wang (Archives of Virology, 2019)

Interaction of MTHFR gene with smoking and alcohol use and haplotype combination susceptibility to psoriasis in Chinese population - Quan Luo; Jingxin Zeng; Wei Li; Ling Lin; Xin Zhou; Xin Tian; Weiyu Liu; Lidan Zhang; Xibao Zhang (Immunologic Research, 2018)

The Vibrio parahaemolyticus-infecting bacteriophage qdvp001: genome sequence and endolysin with a modular structure - Weiyu Wang; Mengzhe Li; Hong Lin; Jingxue Wang; Xiangzhao Mao (Archives of Virology, 2016)

Co-remediation of cadmium-polluted soil using stainless steel slag and ammonium humate - Lin Zhuo; Hua Li; Fangqin Cheng; Yonglin Shi; Qiuhua Zhang; Weiyu Shi (Environmental Science and Pollution Research, 2012)

Influence of the Saharan Air Layer on Atlantic tropical cyclone formation during the period 1–12 September 2003 - Weiyu Pan; Liguang Wu; Chung-Lin Shie (Advances in Atmospheric Sciences, 2011)